2011
DOI: 10.1590/s1516-35982011000900027
|View full text |Cite
|
Sign up to set email alerts
|

Curtain color and lighting program in broiler production: II. carcass and parts yield and abdominal fat deposition

Abstract: -The objective of the present study was to evaluate carcass and parts' yield, abdominal fat deposition and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Whereas, significant differences were observed in the relative weights of the thigh, wings, and neck parts in the seventh week, especially for treatment T3 (17 hours of light: 3 hours of darkness: 1 hour of light: 3 hours of darkness) in which the relative weight of these pieces increased compared to the control treatment, and the reason may be due to the significant decrease in relative weight chest part in this treatment and may have had a role in influencing the growth of other parts. These results agreed with Abreu et al (2011b), who indicated that the use of intermittent lighting had a significant effect on the relative weight of the thigh. As for the relative weight of abdominal fat, the same table indicates that there are no significant differences when using different lighting systems, and these results are in agreement with those obtained by Olanrewaju et al (2012Olanrewaju et al ( -2018.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Whereas, significant differences were observed in the relative weights of the thigh, wings, and neck parts in the seventh week, especially for treatment T3 (17 hours of light: 3 hours of darkness: 1 hour of light: 3 hours of darkness) in which the relative weight of these pieces increased compared to the control treatment, and the reason may be due to the significant decrease in relative weight chest part in this treatment and may have had a role in influencing the growth of other parts. These results agreed with Abreu et al (2011b), who indicated that the use of intermittent lighting had a significant effect on the relative weight of the thigh. As for the relative weight of abdominal fat, the same table indicates that there are no significant differences when using different lighting systems, and these results are in agreement with those obtained by Olanrewaju et al (2012Olanrewaju et al ( -2018.…”
Section: Discussionsupporting
confidence: 91%
“…Lighting programs can affect many aspects of avian physiology, welfare, behavior, and other factors, including blood chemistry, ocular development, and behavioral rhythms (Olanrewaju et al, 2006(Olanrewaju et al, , 2013Schwean-Lardner et al, 2013). Abreu et al (2011b) reported that carcass and thigh weight were heavier when using the intermittent light program. As well as improving the quality of the carcass (Zdenka et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cave et al (1985) reported that males raised under IL had higher abdominal fat content than female broilers; however, other report indicated that the abdominal fat pad contents of broilers reared under IL were significantly less than those of broilers exposed to CL (Buyse et al, 1996). In contrast, Abreu et al (2011) did not observe differences in abdominal fat deposition between IL and CL programme. Based on these research results, it could be inferred that abdominal fat content might be affected by several factors, such as lighting time, photoperiod, sex, age, and breed.…”
Section: Slaughter Performancementioning
confidence: 87%
“…Zdenka et al (2011) observed that an IL regime is justified from the standpoint of carcass quality improvement. In addition, Abreu et al (2011) found that IL programme promoted the highest drumstick and thigh yields. Cave et al (1985) reported that males raised under IL had higher abdominal fat content than female broilers; however, other report indicated that the abdominal fat pad contents of broilers reared under IL were significantly less than those of broilers exposed to CL (Buyse et al, 1996).…”
Section: Slaughter Performancementioning
confidence: 98%
“…These findings partially agree with those reported by Farghly and Makled (2015) who they found that flash lighting significantly affected on liver percentages. And, Abreu et al, (2011) who showed that lighting programs did not affect the heart, liver, gizzard, and abdominal fat percentages.…”
Section: Discussionmentioning
confidence: 99%